(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
More parents are opting to homeschool their children rather of sending them to public or private schools. Find out more about the homeschooling movement and what it entails when parents teach their children at home. Homeschooling is a rising trend in which parents teach their kids at homes instead of transferring kids to a traditional government or private school. Parents homeschooling for a variety of reasons, including dissatisfaction with educational options, cultural or educational differences, and the notion that children do not develop properly in the traditional school system. In the 1970s, a number of well-known authors and scholars, including John Holt, Dorothy Moore, and Raymond Moore, started writing concerning educational change, the homeschooling movement took off. They advocated for homeschooling as a viable educational choice. In the Western States, the general public sees and writes about homeschooling children who win or place highly in international vocabulary and geography competitions; homeschooling kids who enrol in prestigious colleges; and how schools are now seeking and accepting homeschooled kids. They look at the results of many studies that compare homeschoolers’ academic achievement to that of their public school counterparts. Moreover, during the last several years, the movement has been gradually expanding.